Structural premise of selective deubiquitinase USP30 inhibition by small-molecule benzosulfonamides - O'Brien, DP; Jones, HBL; Guenther, F; Murphy, EJ; England, KS; Anderson, M; Brennan, P; Davis, JB; Pinto-Fernandez, A; Turnbull, AP; Kessler, BM (2022)
Dampening functional levels of the mitochondrial deubiquitylating enzyme USP30 has been suggested as an effective therapeutic strategy against neurodegenerative disorders such as Parkinson’s Disease. USP30 inhibition may counteract the deleterious effects of impaired turnover of damaged mitochondria which is inherent to both familial and sporadic forms of the disease. Small-molecule inhibitors targeting USP30 are currently in development, but little is known about their precise nature of binding to the protein. We have integrated biochemical and structural approaches to gain novel mechanistic insights into USP30 inhibition by a small-molecule benzosulfonamide containing compound, 39. Activity-based protein profiling (ABPP) mass spectrometry confirmed target engagement, the high selectivity, and potency of 39 for USP30 against 49 other deubiquitylating enzymes in a neuroblastoma cell line. In vitro characterization of 39 enzyme kinetics infers slow and tight binding behavior, which is comparable with features of covalent modification of USP30. Finally, we blended hydrogen-deuterium exchange mass spectrometry and computational docking to elucidate the molecular architecture and geometry of USP30 complex formation with 39, identifying structural rearrangements at the cleft of the USP30 thumb and palm subdomains. These studies suggest that 39 binds to the thumb-palm cleft that guides the ubiquitin C-terminus into the active site, thereby preventing ubiquitin binding and isopeptide bond cleavage, and confirming its importance in the inhibitory process. Our data will pave the way for the design and development of next-generation inhibitors targeting USP30 and associated deubiquitinylases.